Peningkatan Talenta Manajemen Aparatur Desa Dalam Menyusun Laporan Pertanggungjawaban Keuangan Desa Di Desa Mulyasari Kecamatan Banjar Patroman Kota Banjar - Ridho Harta; Bambang Agus Diana; Dwi Putranto Riau; Tora Akadira (Jurnal Pengabdian kepada Masyarakat Radisi, 2022)
Talent Management (TM) emerged as a way to build human capacity. For public and private organizations. Building human capacity is the main thing to achieve organizational goals and improve performance. Talent management is how to develop Human Resources (HR). Talent Management as a tool to filter and map employees who have the best talent. HR is managed in a directed and sustainable manner. The purpose of this activity is how to increase the management talent of village officials, especially in compiling digital-based financial accountability reports in the Mulyasari Village government, Pataruman District / Banjar City. This activity method uses (1) the Participatory Rural Appraisal (PRA) model; (2) Participatory Technology Development Model; (3) Community Development Model; (4) Persuasive; and (5) Educational. The research design is a qualitative case study. Technical implementation of preparation activities, implementation of activities and evaluation